2010
DOI: 10.1016/j.infbeh.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Premature infant swallowing: Patterns of tongue-soft palate coordination based upon videofluoroscopy

Abstract: Coordination between movements of individual tongue points, and between soft palate elevation and tongue movements, were examined in 12 prematurely born infants referred from hospital NICUs for videofluoroscopic swallow study (VFSS) due to poor oral feeding and suspicion of aspiration. Detailed post-evaluation kinematic analysis was conducted by digitizing images of a lateral view of digitally superimposed points on the tongue and soft palate. The primary measure of coordination was continuous relative phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…As in our previous report [18], tongue and soft palate coordination during preterm infant swallowing was organized around stable in-phase and antiphase patterns. There may be a functional basis for the organization of the oral anatomy into patterns of in-phase and antiphase.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…As in our previous report [18], tongue and soft palate coordination during preterm infant swallowing was organized around stable in-phase and antiphase patterns. There may be a functional basis for the organization of the oral anatomy into patterns of in-phase and antiphase.…”
Section: Discussionsupporting
confidence: 52%
“…In a previous study, for example, we [18] found that the timing of tongue and soft palate appears to be attracted to certain stable coordination patterns. Three tongue points (anterior, medial, and posterior) were organized around a stable in-phase pattern, with a phase lag that implied an anterior–posterior direction of motion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In adults and children such dysphagia are usually investigated using Videofluroscopic Swallow Study (VFSS), or the Fiberoptic Endoscopic Evaluation of Swallowing (FEES). FEES has been proved in several studies to be of equivalent diagnostic value as VFSS . FEES uses transnasal flexible fiberoptic laryngoscopy to view the pharynx and larynx during swallowing without interfering in the physiology of respiration.…”
Section: Introductionmentioning
confidence: 99%
“…This intricate array of fibers, aligned at various angles orthogonal to the direction of deformation, may be the structural basis for what is called hydrostatic deformation. For example, during human swallowing, a series of deformations results in the transport of ingested food from the mouth to the esophagus (Goldfield et al, 2010;Miller, 1993). How do large numbers of fibers of varying alignments achieve the mechanical functions of swallowing, such as containing the bolus in a grooved depression in the middle portion of the tongue's dorsal surface, transferring the bolus to the posterior oral cavity, and propelling the bolus to the pharynx?…”
Section: Soft Animals Hydrostatic Organs and Soft Robotsmentioning
confidence: 99%